Cloudy - background and prop design exploration - Teoh, Renee Hui Yi (Nanyang Technological University, 2023)
“Cloudy” is a 2D animated short that aims to explore the relationship between adults and their parents – from dealing with the internal conflict of being vulnerable and upholding expectations of self-reliance, to finding security in one’s unity with their family. This is done through a man’s journey of opening up to his mother about his predicament of being fired – through the parallel adventure of helping Cloudy, a small sentient cloud that is looking for its mother.